Pengaruh Voluntary Disclosureterhadap Kualitas Laba pada Laporan Keuangan Bank Umum Syariah di Indonesia Priode 2017-2021 - Ismaydina, Putri (CV. Kalimasada Group, 2023)
This research aims to find out and analyze whether Voluntary disclosure has an effect on the quality of earnings in the Financial Reports of Sharia Commercial Banks in Indonesia (Period 2017-2021). The independent variable used in this research is Voluntary Disclosure, while the dependent variable is earnings quality. The method in this research uses quantitative data. The data used as reference material for this research is research data obtained from Sharia Commercial Banks which includes profit data and Voluntary disclosure. The sample collection technique in this research was carried out using a purposive sampling method with predetermined criteria. The population in this research is 14 sharia commercial banks in Indonesia. The samples in this research were Islamic commercial banks in Indonesia, totaling 6 samples. The results of this research state that Voluntary Disclosure on Profit Quality in Sharia Commercial Banks states that tcount > ttable, namely 2.494> 0.017 and tcount is in the Ha acceptance area and so H0 is rejected (Ha is accepted). This states that Voluntary Disclosure has a partially significant effect on the Quality of Profits in Sharia Commercial Banks